Lip and tooth injuries at public swimming pools in Austria. Issue 3 (10th April 2017) - Lechner, Katharina; Connert, Thomas; Kühl, Sebastian; Filippi, Andreas
Abstract: Background/Aims: There is an increased risk of orofacial injuries in swimming pool facilities. Nevertheless, only a few studies have addressed this issue. The aim of this study was to identify the frequency of lip and tooth injuries at public swimming pools in Austria. A further aim was to examine which gender and age groups were affected, where and why these injuries occurred, and whether pool attendants had sufficient knowledge of dental first‐aid measures. Material and methods: A total of 764 pool attendants in Austria were contacted by telephone and 689 participated in the study (90.2%). The attendants were interviewed retrospectively about accident occurrences in 2014 by a standardized questionnaire. Responses to the provision of first aid and choice of storage medium for avulsed teeth were subsequently evaluated. Results: The frequency of lip injuries was 19.0%, and tooth injuries were 11.3%. Male bathers ( P < .05) and children under 12 years ( P < .001) most frequently suffered injuries. The waterslide was the most common accident site. The most common cause of lip injuries was slipping on wet surfaces (39.0%), and for tooth injuries it was collisions with other persons or objects (each 28.1%). The pool attendants' responses were predominantly good or sufficient on first aid, with the exception of what storage medium to choose. Tooth rescue boxes were available in only 8.6% of all pool facilities. Conclusion: Orofacial injuries are a frequently occurring problem in swimming pool facilities. The pool attendants' knowledge on first‐aid care of tooth injuries could still be improved.